Use Of Voceblary Translation Strategieis: A Semantic Translation Analysis - Todjidinova Umida Urinboy qizi (Academia One, 2024)
Interpretation is the most common way of moving source language instant messages into the objective language. The commonsense target of the message move process is to help the peruser of the objective language message in understanding the message expected by the first creator ofthe source language text. There are many kinds of interpretations accessible, yet at the same semantic interpretation is viewed as the kind of interpretation that is the most reliable in conveying meaning. Semantic interpretation attempts to redirect as intently as conceivable the semantic and syntactic designs of the objective language with precisely the same context oriented significance in the source language message, as well as word implications and sentence implications from the point of view of the source text setting. Semantic interpretation is viewed as the most adaptable what's more, adaptable interpretation
Keywords: contextual meaning; message redirection process; semantic structure; syntax